Evaluation of platelet indices in dengue fever in a tertiary care hospital in Bangladesh - Paul, Debatosh; Pramanik, Amit K.; Biswas, Sanchita; Das, Chitra; Islam, Mohammad T. (International Journal of Advances in Medicine, 2023)
Background: Dengue fever is the most rapidly spreading mosquito-borne viral diseases in the world. Some evidence suggests that platelet indices may have diagnostic and prognostic value in Dengue fever. The aim of the study is to evaluate platelet indices and to find their correlation between platelet count in Dengue fever. Methods: This retrospective cross-sectional study was conducted through the use of stored data in Bangabandhu Sheikh Mujib Medical University (BSMMU) dengue cell from July 2019 to September 2019 at department of laboratory medicine and department of internal medicine, BSMMU, Dhaka. Among them, clinical records of 260 cases are preserved in a structured clinical record form (CRF). After ethical clearance from institutional review board (IRB), form clinical records of 260 cases which were preserved in a structured CRF patients who fulfilled the inclusion and exclusion criteria was selected as study population. Results: Platelet indices (MPV and PDW) were statistically significant difference among different platelet counts (p<0.05). There was significant negative correlation between platelet count and PDW (r=-0.228, p≤0.001). There was also negative correlation between platelet count and MPV (r=-0.106) which was not statistically significant (p=0.088). Conclusions: Platelet indices are useful parameters in dengue infection. Other than platelet count, PDW and MPV are useful to monitor dengue fever.